Sustainable horizons a landscape-based approach to the sustainable tourism master plan of Mariveles, Bataan - Atienza, Nesslee A.; Madonna P. Danao; Honorio Palarca (Quezon City College of Architecture, University of the Philippines Diliman, 2025)
Mariveles is a coastal municipality in Bataan with significant natural and historical values. However, it is also known for its industrial sector which is continuously expanding and thus, presenting risks to the municipality’s ecological integrity. Tourism, an emerging sector in Mariveles due to its resources, presents as a potential gateway for the municipality’s sustainable development. Thus, this study aims to develop a tourism master plan anchored by sustainability principles that balances ecological integrity, cultural and heritage preservation, and community well-being. Moreover, the study aims to achieve this through the application of a landscape-based approach to sustainable tourism planning. Through a multidisciplinary methodology using landscape analysis, stakeholder, experts, and tourists engagement, and scenario building, three sustainable tourism scenarios were derived. A sustainability compliance criteria was used to score the three scenarios. Ultimately, the Natural and Cultural-Heritage Led Tourism model prioritizing community-based ecological and heritage preservation emerged as the most sustainable and context suitable. The final master plan emphasized priority points of landscape-based zoning, adaptive reuse, climate-adaptive public spaces, and low impact strategies. A boardwalk network along the coastline of Mariveles was also proposed to exhibit the master plan’s objectives. Overall, the study underscores that this model of landscape driven tourism planning can address environmental and heritage degradation, and facilitate economic growth and community engagement. Lastly, the study recontextualizes sustainable tourism as not only a model for attracting visitors but for regenerating landscapes, providing identity, and empowering communities.
Include appendices
Thesis (Bachelor of Landscape Architecture) -- University of the Philippines Diliman
Keywords: Sustainable tourism -- Mariveles (Bataan); Sustainable development -- Landscape architecture -- Mariveles (Bataan); Community-based tourism -- Mariveles (Bataan); Landscape design -- Mariveles (Bataan)